Integration of a neuronal RNAseq dataset with the draft Gryllus bimaculatus transcriptome refines gene predictions and highlights potential systematic response to injury - Felicia F. Wang; Harrison P. Fisher; Lisa M. Ledwidge; Joel H. Graber; Riley A. Grindle; Jarod A. Rollins; Hadley W. Horch (PLoS ONE, 2026)
The cricket Gryllus bimaculatus presents a compelling model for investigating neuroplasticity due to its unusual capability of adult structural reorganization. The molecular pathways underlying these changes remain poorly understood. Here, we reanalyzed RNAseq data, originally collected from deafferented and control prothoracic ganglia one, three, and seven days post-injury, which had previously been used to assemble a de novo transcriptome. In this current analysis, we aligned our original RNAseq data to the publicly available G. bimaculatus draft genome, and used the resulting alignments to refine and update the existing annotations. The integration added 3,868 novel genes, 9,172 new transcript isoforms including both protein-coding and putative non-coding transcripts, reflecting the likely regulatory importance of long non-coding RNAs in this neuronal context. These updated annotations were used as the basis for a DESeq2 differential expression analysis and subsequent functional enrichment analysis to further explore the potential molecular basis of this compensatory anatomical plasticity. Days one and three showed the largest post-deafferentation expression differences. Overall, more transcripts were upregulated rather than downregulated. Protein-protein associations enriched for GTPase-related signaling, hormone metabolism, and membrane dynamics were evident. We also identified a surprising enrichment of gene ontology terms related to muscle contraction in this neuronal-specific transcriptome. Toll receptor signaling emerged as a candidate pathway warranting further investigations. Our results demonstrate the importance of updating the reference transcriptome for analysis of highly specialized tissues or conditions, and serve as a resource for generating testable hypotheses about the well-conserved molecular mechanisms that may underlie this unique example of adult structural plasticity in the cricket.